Desenvolvimento de sistema web para gerenciar o fluxo de veículos no departamento de logística - Padilha, Cleocir (2011)
This paper proposes the development of software as an alternative to manage the flow of vehicles, operations and processes pertaining to loading and unloading carried out by the logistics department, the solution provides statistical data regarding the times for each process area managers with purpose of increasing its efficiency. We opted for a solution to web according to the flexibility offered in software maintenance, and especially the possibility of linking raw material suppliers, customers and end consumers. The programming language used is PHP, chosen by the rapid learning and servers run on Linux, very common in many providers, we can cite the benefits of low cost and easy setup. The business rule was drafted in the database as the purpose of facilitating the maintenance of codes in the interface.